Exfoliative Esophagitis and it's differential diagnostic considerations Exfoliative Ösophagitis und ihre differenzialdiagnostischen Überlegungen - Veits, L.; Kalinski, R.; Vieth, M.; Sterlacci, W. (Endoskopie heute, 2013)
The exfoliation of the mucosa of the esophagus is usually an impressive clinical finding, and represents a common symptom of various, often etiologically diverse diseases. We present a clinically and endoscopically typical case of exfoliative esophagitis and briefly discuss possible underlying diseases, thereby providing assistance for differential diagnostic considerations in daily practice.©Georg Thieme Verlag KGStuttgart New York.
CRIS-Team Scopus Importer:2025-03-05
Keywords: dissection; esophagitis dissecans superficialis; exfoliative esophagitis; mucosa